Mixed boundary-value problem for linear second-order nondivergent parabolic equations with discontinuous coefficients - Guliyev, A.F.; Ismayilova, S.H. (Український математичний журнал, 2014)
The mixed boundary-value problem is considered for linear second-order nondivergent parabolic equations with discontinuous coefficients satisfying the Cordes conditions. The one-valued strong (almost everywhere) solvability of this problem is proved in the space Ŵ2,1p, where p belongs to the same segment containing point 2.